Manajemen Perpustakaan di Sekolah Dasar Negeri Nagrak 02 Kecamatan Sukaraja Kabupaten Bogor - Siti Maylani Tineke; Ahmadi Sukarno; Ariah; Setia Budi (STIT Fatahillah, 2024)
The objective of the research is to know: 1. How is school library management as a student’s learning resource in sdn nagrak 02 : what are the supporting factors and any obstacles in using school library as a student’s learning resource in sdn nagrak 02. It is observational research by using descriptive qualitatif method. Interviewing, observation, and documentation are used to get the data. The result of the research stated that the library itself as the main tool for managing a school library is not available in SDN Nagrak 02. This is because there is no room or space for a library that has the same large as the government standard. The collection of the class library in SDN Nagrak 02 is limited. There are only textbooks and teacher reference books. The school still has plans to have a library in its own space. Even it is still limited. In using a library, teachers maximize to use of the available facility as a learning resource for students. The ways are, the books are used in the teaching and learning process in the classroom. They are lent and can be brought home. The reading activity before the teaching and learning process in SDN Nagrak 02 has several factors. They are the class library, school librarian, also teacher’s spirit and creativity. Besides that, there are some inhibitors such as, the school hasn’t had a space for a school library yet, and the collection of the book is limited.